ANALISIS KETIMPANGAN SUPLAI GIZI GLOBAL MENGGUNAKAN PENDEKATAN BUSINESS INTELLIGENCE BERBASIS VISUALISASI INTERAKTIF - Danendra, Steven; Aryandi, Demitri Fernando Putra; Wicaksono, Soetam Rizky (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
The COVID-19 pandemic has caused significant changes in global food consumption patterns, impacting the balance of macronutrient intake and overall public health. This study is motivated by the need to understand the global distribution and disparity of nutrition supply, which may affect food security and metabolic disease risk. The objective of this research is to analyze per capita calorie, protein, and fat supply across countries and examine its relation to health issues such as obesity and COVID-19 mortality. The methodology uses a Business Intelligence approach involving the ETL (Extract, Transform, Load) process applied to a global nutrition dataset from Kaggle, which is then visualized through five interactive dashboards using Looker Studio. The results indicate that high nutrient supply does not necessarily originate from economically dominant countries, and regional disparities remain prominent—particularly in developing countries that rely heavily on cereals and vegetable oils. Furthermore, the analysis found no strong correlation between nutritional adequacy and obesity or COVID-19 mortality rates, suggesting the influence of external factors such as lifestyle and healthcare infrastructure. This study concludes that interactive data visualization can provide deeper spatial and thematic insights into global nutrition challenges and serve as a data-driven decision support tool in the fields of public health and nutrition policy.